Bonobos point more for ignorant than knowledgeable social partners - Luke A. Townrow; Christopher Krupenye (Proceedings of the National Academy of Sciences, 2025)
Numerous uniquely human phenomena, from teaching to our most complex forms of cooperation, depend on our ability to tailor our communication to the knowledge and ignorance states of our social partners. Despite four decades of research into the “theory of mind” capacities of nonhuman primates, there remains no evidence that primates can communicate on the basis of their mental state attributions, to enable feats of coordination. Moreover, recent reevaluation of the experimental literature has questioned whether primates can represent others’ ignorance at all. The present preregistered study investigated whether bonobos are capable of attributing knowledge or ignorance about the location of a hidden food reward to a cooperative human partner, and utilizing this attribution to modify their communicative behavior in the service of coordination. Bonobos could receive a reward that they had watched being hidden under one of several cups, if their human partner could locate the reward. If bonobos can represent a partner’s ignorance and are motivated to communicate based on this mental state attribution, they should point more frequently, and more quickly, to the hidden food’s location when their partner is ignorant about that location than when he is knowledgeable. Bonobos indeed flexibly adapted the frequency and speed of their communication to their partner’s mental state. These findings suggest that apes can represent (and act on) others’ ignorance in some form, strategically and appropriately communicating to effectively coordinate with an ignorant partner and change his behavior.